Game Theory: An Overview of Natural Resource Conflict and its Resolution - Kunwar, Sajin (Journal of APF Command and Staff College, 2025)
This article illustrates the concept of irrigation conflict and its resolution practices in the Khageri irrigation project that lies in the Chitwan district of Nepal. The author collected data from the informants of the study area who were farmers, members of water user associations, civil society, and local government officials. Some issues of conflict while managing the irrigation project were the denial of riparian rights, resource rights dilemma, water scarcity, human encroachment of the canal, park control, legal restrictions and raising water fees, called ‘pani pot’ in its colloquial term. The resolution of such conflict, as per the findings of this paper, reflects the importance of co-management and cooperation among all the users. Some elderly farmers act as a mediator to resolve the conflicting issues. There were some farmers who adjudicate cases of conflict for the local administration and police station. Author highlighted the game theory model that is effective for the wise use of natural resources in general and irrigation management in particular.